Misoprostol for primary versus secondary prevention of postpartum haemorrhage: a cluster‐randomised non‐inferiority community trial. (1st September 2015) - Raghavan, S; Geller, S; Miller, S; Goudar, SS; Anger, H; Yadavannavar, MC; Dabash, R; Bidri, SR; Gudadinni, MR; Udgiri, R; Koch, AR; Bellad, MB; et al.
Abstract : Objective: To assess whether secondary prevention, which preemptively treats women with above‐average postpartum bleeding, is non‐inferior to universal prophylaxis. Design: A cluster‐randomised non‐inferiority community trial. Setting: Health sub‐centres and home deliveries in the Bijapur district of Karnataka, India. Population: Women with low‐risk pregnancies who were eligible for delivery with an Auxiliary Nurse Midwife at home or sub‐centre and who consented to be part of the study. Methods: Auxiliary Nurse Midwifes were randomised to secondary prevention using 800 mcg sublingual misoprostol administered to women with postpartum blood loss ≥350 ml or to universal prophylaxis using 600 mcg oral misoprostol administered to all women during the third stage of labour. Main outcome measures: Postpartum haemoglobin ≤7.8 g/dl, mean postpartum blood loss and postpartum haemoglobin, postpartum haemorrhage rate, transfer to higher‐level facilities, acceptability and feasibility of the intervention. Results: Misoprostol was administered to 99.7% of women as primary prevention. In secondary prevention, 92 (4.7%) women had postpartum bleeding ≥350 ml, of which 90 (97.8%) received misoprostol. The proportion of women with postpartum haemoglobin ≤7.8 g/dl was 5.9 and 8.8% in secondary and primary prevention clusters, respectively [difference −2.9%, one‐sided 95% confidence interval (CI) <1.3%]. Postpartum transfer and haemorrhage rates were low (<1%) in both groups. Shivering was more common in primary prevention clusters ( P  = 0.013). Conclusion: Secondary prevention of postpartum haemorrhage with misoprostol is non‐inferior to universal prophylaxis based on the primary outcome of postpartum haemoglobin. Secondary prevention could be a good alternative to universal prophylaxis as it medicates fewer women and is an acceptable and feasible strategy at the community level. Tweetable abstract: Secondary prevention of postpartum haemorrhage with misoprostol is non‐inferior to universal prophylaxis. Tweetable abstract: Secondary prevention of postpartum haemorrhage with misoprostol is non‐inferior to universal prophylaxis.